Diseño de un sistema de gestión de calidad bajo la norma ISO 9001:2008 en el ámbito técnico administrativo financiero de la facultad de arquitectura y diseño de la universidad católica de santiago de Guayaquil - Romero Mendoza, Ana María (2010)
To enforce the organizational culture aligned to quality standards and offer reliable support to the development of academic management” is the purpose of the Faculty of Architecture and Design´s Strategic Plan, from its technicaladministrative and financial perspective. This reveals the need to put into practice a Quality Management System according to ISO 9001:2008 norms that contributes to the achievement of the proposed goals. In order to obtain a diagnosis of the current situation and estimate the fulfillment of the established norms, an Internal Audit is executed. In addition, a Process Map is prepared once local procedures are evaluated, allowing to determine the existence of correlations inside the unit. To focus on process and service improvement, Policies and Quality Objetives are created. A work methodology is proposed to improve process and procedures, as well as the implementation of the non existing ones; through the design of the Documentary System and Quality Manuals and Procedures. The intention of this document is to provide a management tool based on specific quality standards, adjusting the requirements and expectations of clients to achieve service excellence.